2002
DOI: 10.1161/01.str.0000039405.31526.06
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nonpeptide V 1 Vasopressin Receptor Antagonist SR-49059 on Infarction Volume and Recovery of Function in a Focal Embolic Stroke Model

Abstract: Background and Purpose-Cerebral edema develops very early after the onset of focal cerebral ischemia and may be a major factor in early disability after an acute ischemic stroke. There have been very limited studies on the usefulness of antiedemic agents as neuroprotective agents in the setting of focal cerebral ischemia. We tested the neuroprotective effects of a new potent nonpeptide vasopressin receptor V 1 antagonist, SR-49059, in a focal embolic stroke model in rats. Methods-Focal ischemic injury was indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 42 publications
2
79
0
1
Order By: Relevance
“…The volume of infarct was calculated using the following formula: infarct volume = (volume of left hemisphereÀ(volume of right hemisphere Àmeasured infarct volume))/volume of left hemisphere. The brain swelling was determined using the following formula: swelling (edema) = (volume of right hemisphereÀvolume of left hemisphere)/volume of left hemisphere (Shuaib et al, 2002).…”
Section: Ischemic Lesion Size Measurementmentioning
confidence: 99%
“…The volume of infarct was calculated using the following formula: infarct volume = (volume of left hemisphereÀ(volume of right hemisphere Àmeasured infarct volume))/volume of left hemisphere. The brain swelling was determined using the following formula: swelling (edema) = (volume of right hemisphereÀvolume of left hemisphere)/volume of left hemisphere (Shuaib et al, 2002).…”
Section: Ischemic Lesion Size Measurementmentioning
confidence: 99%
“…The method for quantification of infarct volume was performed exactly as previously reported [25,66,78]. Briefly, after completing the neurological evaluation and the rotarod test at 3 days after transient FCI, the animals were sacrificed under deep anesthesia and brains were removed, frozen and coronally sectioned into six 2-mm-thick slices (from rostral to caudal, first to sixth).…”
Section: Quantification Of Brain Infarct Volumementioning
confidence: 99%
“…Further, experimental models of intracerebral hemorrhage, middle cerebral artery occlusion, ischemia, and cold and traumatic brain injury have demonstrated that V1aR inhibition reduces brain edema. [22][23][24][25][26][27][28][29][30][31] The underlying mechanism of this response has been attributed to either modulation of vasopressin in the brain parenchyma 17 or its interaction with aquaporin-4 (AQP4). AQP4 is the predominant water channel in the brain and has a significant role in the pathophysiology of brain edema.…”
Section: Introductionmentioning
confidence: 99%